The Side-Hustle: An Emergent Typology of Entrepreneurs as Employees - Walsh, Kevin; Stephens, Simon (Senate Hall, 2022)
In this paper we present the experiences of high-tech entrepreneurs who have become employees in high-tech companies. The entrepreneurs in this study are all hybrid entrepreneurs who returned to full-time employment and continued to engage in what we define as ‘side-hustles’. An emerging, albeit small, body of literature around the term side-hustle uniquely captures the combination of, often informal, entrepreneurial activity performed alongside a foundation of full-time employment. Fifteen interviews were conducted online during July and August 2020. Our analysis of the interviews supports the development of a typology of entrepreneurial employees. Specifically, our findings indicate that there are three types of employees who engage in side-hustles: transient, reluctant, and autonomous entrepreneurial employees. Each of the three types engage with side-hustles differently, depending on their background, motivations for returning to employment and their entrepreneurial mindset. The typology can be used to compare differences in attitudes and abilities towards employment. We also provide insights into managerial implications in relation to the supports needed to recruit, engage and retain entrepreneurs as employees. This is an important issue because treating employees who engage in side-hustles as a homogenous group may result in a misunderstanding of the diversity of impacts that they have on an organization.
Keywords: entrepreneurs|employees|intrapreneurship|typology|side-hustle